2012
DOI: 10.1583/jevt-11-3702r.1
|View full text |Cite
|
Sign up to set email alerts
|

Complication Rate of the Fascia Closure Technique in Endovascular Aneurysm Repair

Abstract: The fascia closure technique during EVAR is safe and has few complications. The low frequencies of pseudoaneurysms and other access site complications make the femoral closure technique a durable alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The 91% success rate of the FST in this study was similar to that described in other studies. 105,195,200 Compared to other methods of closing the femoral access sites after EVAR it offers similar safety and complication rates. Numerous trials evaluate the preclose method (double ProStarXL ® ) for closure of femoral access sites.…”
Section: Short and Mid-term Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 91% success rate of the FST in this study was similar to that described in other studies. 105,195,200 Compared to other methods of closing the femoral access sites after EVAR it offers similar safety and complication rates. Numerous trials evaluate the preclose method (double ProStarXL ® ) for closure of femoral access sites.…”
Section: Short and Mid-term Resultsmentioning
confidence: 99%
“…Other studies have also reported postoperative pseudoaneurysms after FST ranging from 3% -13.9%. 105,195,200 The reported intervention rate at 1 year was however <1%. It should be noted that the presence of these small pseudoaneurysms could pose a potential danger for late complications if they should grow in size.…”
Section: Pseudoaneurysmsmentioning
confidence: 95%
“…In this study, there were no anatomical exclusion criteria such as high bifurcation of the CFA, and the thickness of the fat overlying the CFA did not compromise the success of the technique. In the same period, Mathisen et al 49 reviewed their results in a retrospective study, which included 49 patients (81 femoral access sites). The CFA was detected using palpation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the FST group, technical success was defined as the achievement of hemostasis with adequate distal perfusion within the first 24 hours without femoral occlusion or use of additional fascial sutures. 15,[46][47][48][49][50] Any complication (bleeding and/or thrombosis) that leads to additional procedure within 24 hours was classified as intraoperative complication, whereas complications, such as bleeding, thrombosis, pseudoaneurysm, stenosis, neuralgia, seroma, and local infection, that took place after 24 hours were considered postoperative.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation